2005
DOI: 10.1128/aem.71.6.3025-3032.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Endopeptidase Genes from the Genomic Sequence of Lactobacillus helveticus CNRZ32 and the Role of These Genes in Hydrolysis of Model Bitter Peptides

Abstract: Genes encoding three putative endopeptidases were identified from a draft-quality genome sequence of Lactobacillus helveticus CNRZ32 and designated pepO3, pepF, and pepE2. The ability of cell extracts from Escherichia coli DH5␣ derivatives expressing CNRZ32 endopeptidases PepE, PepE2, PepF, PepO, PepO2, and PepO3 to hydrolyze the model bitter peptides, ␤-casein (␤-CN) (f193-209) and ␣ S1 -casein (␣ S1 -CN) (f1-9), under cheese-ripening conditions (pH 5.1, 4% NaCl, and 10°C) was examined. CNRZ32 PepO3 was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
3
31
2
3
Order By: Relevance
“…helveticus CNRZ32 has been previously reported (Chen et al, 2003;Sridhar et al, 2005). In contrast to our findings, Sridhar et al (2005) reported that PepO of Lb. helveticus CNRZ32 did not possess activity on b-CN f193-209 under cheese ripening conditions (pH 5.1, 4% NaCl, and 10 1C).…”
Section: Article In Presscontrasting
confidence: 85%
See 2 more Smart Citations
“…helveticus CNRZ32 has been previously reported (Chen et al, 2003;Sridhar et al, 2005). In contrast to our findings, Sridhar et al (2005) reported that PepO of Lb. helveticus CNRZ32 did not possess activity on b-CN f193-209 under cheese ripening conditions (pH 5.1, 4% NaCl, and 10 1C).…”
Section: Article In Presscontrasting
confidence: 85%
“…PepE did not show activity on b-CN f193-209, in agreement with Sridhar et al (2005). Table 5 lists mass-to-charge ratios (m/z) of MALDI-TOF peaks resulting from the combined action of CFEs from E. coli DH5a derivatives expressing PepE and PepN of Lb.…”
Section: Degradation Of B-cn F193-209 By Pepe-pepn Pepe-pepo Like Ensupporting
confidence: 79%
See 1 more Smart Citation
“…Post-proline cleaving ability was detected for three enzymes (PepO2, PepO3, and PepF), PepO2 having the highest activity. Based on sequence comparison, PepO2 and PepO3 were also predicted to be metalloendopeptidases [52,53]. Recombinant L. helveticus PepO2, cloned and expressed in Escherichia coli, did not reveal activity against proline-rich, gluten-derived oligopeptides.…”
Section: Other Proline-specific Endopeptidasesmentioning
confidence: 99%
“…Even though the proteolytic system of L. helveticus (Christensen, Dudley, Pederson, & Steele, 1999) and the ability of this microorganism to hydrolyze bitter peptides (Christensen, Broadbent, & Steele, 2003;Sridhar, Hughes, Welker, Broadbent, & Steele, 2005) have been studied intensively in recent years, understanding of the specific enzymes responsible for the generation and stability of ACEinhibitory peptides is lacking. To evaluate the contributions of individual enzymes to peptide processing, it is necessary to construct recombinant L. helveticus strains differing only in the activity of known components of the proteolytic mechanism.…”
Section: Introductionmentioning
confidence: 99%